Hubungan Soft Skill, Minat Kerja dan Hard Skill dengan Kesiapan Kerja Mahasiswa - Indriyani; Fitri, Kurniawaty; Rifqi, Ahmad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Work readiness reflects how well an individual is physically, mentally, and experientially prepared to perform tasks relevant to their field of expertise. In theory, soft skills, career interests, and hard skills are considered influential factors in students’ work readiness when facing the challenges of the professional world. This study aims to examine the relationship between these three variables and the work readiness of 2022 cohort students at the Faculty of Economics and Business, University of Riau, who feel prepared to enter the workforce after completing their education. The research was conducted using a quantitative approach with a survey method, which involved distributing questionnaires to 259 respondents selected based on work readiness criteria. The data were analyzed using the Bivariate Pearson correlation test with the assistance of SPSS version 27. The results indicate that soft skills, career interests, and hard skills have a positive and significant impact on students’ work readiness. These findings contribute theoretically by strengthening empirical evidence on the significance of these three factors and offer practical implications for educational institutions and employers in designing learning and training strategies that comprehensively support students’ career readiness.